2022
DOI: 10.1155/2022/1799431
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ficus carica on Male and Female Reproductive Capabilities in Rats

Abstract: The basic purpose of pharmacology is to look into the benefits of natural remedies and make them available to the general populace. Herbal medicines are now considered to be the future of humanity. The current study explored the effects of Ficus carica (FC) extract in rats of two-generation F0 (parents) and F1 (offspring) in either sex. The F. carica extract was initially tested for acute and sub-chronic toxicity. Extracts were also tested for fertility assessment and effects on reproductive hormones like foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several factors that cause this to happen are increased metabolic rate, decreased energy use, and decreased nutritional intake due to reduced appetite, in addition to decreased body weight when hypoxic conditions are caused by the use of adipose tissue as an energy source, due to reduced food intake (Matu et al 2018). In an F. carica study without involving IH exposures, it was found that consuming F. carica extracts at doses of 50 and 100 mg/kg affected weight gain (Ain et al 2022). In this study, it is believed that there was some effect on weight gain, but the presence of IH exposure makes the body focus on maintaining body condition so that it remains constant during the IH exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that cause this to happen are increased metabolic rate, decreased energy use, and decreased nutritional intake due to reduced appetite, in addition to decreased body weight when hypoxic conditions are caused by the use of adipose tissue as an energy source, due to reduced food intake (Matu et al 2018). In an F. carica study without involving IH exposures, it was found that consuming F. carica extracts at doses of 50 and 100 mg/kg affected weight gain (Ain et al 2022). In this study, it is believed that there was some effect on weight gain, but the presence of IH exposure makes the body focus on maintaining body condition so that it remains constant during the IH exposure.…”
Section: Discussionmentioning
confidence: 99%
“…BCR or PRL treatments alone did not affect the LH response [65]. LH acted on mural GCs, yielding high levels of LHR and initiating a series of events leading to cumulus cell expansion and follicle rupture [66]. With the increase in LHR gene expression, the sensitivity of follicles to LH increased, which drove follicular development in the second half of the follicular phase [48,67].…”
Section: Effect Of Prl On the Expression Of Genes At Different Stages...mentioning
confidence: 98%
“…A similar protocol was followed for the female group as well. All rats were dosed for 30 days before mating (Pre-Cohabitation) by gastric gavage between 14:00 and 16:00 h. Female rats were subjected to the soiled bedding of an adult male rat to align their estrus cycle (female rats were fertile and receptive during this period) [49]. During mating each male rats were individually paired with female rats of each group in separate cages for seven days (1:1).…”
Section: Total Phenolic Content Analysismentioning
confidence: 99%